2012
DOI: 10.1007/s11010-012-1338-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone induces cell cycle arrest and apoptosis of multidrug resistant human chronic myeloid leukemia cells by inhibiting the activity of eukaryotic initiation factor 4E

Abstract: Cryptotanshinone (CPT), a diterpene quinone isolated from Salvia miltiorrhiza, is recently reported to have obvious anticancer activities against diverse cancer cells. However, the effect and regulatory mechanism of CPT remain unclear in human chronic myeloid leukemia (CML) cells. In this study, we investigated the antiproliferative activity of CPT on the multidrug resistant CML cells K562/ADM. Our results demonstrated that CPT decreased the cell viability of K562/ADM cells by inducing cell cycle arrest and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…The results from a study by Chen et al suggested that CPT is a potential drug for the treatment and prevention of human lung cancer (25). The results of our previous study indicated that CPT remained potent in tumor cells with an MDR phenotype, suggesting its potential application in cancer exhibiting a high level of chemotherapeutic resistance (12). In the present study, CPT significantly decreased the viability of the BxPC-3 pancreatic cancer cells via the induction of apoptosis and cell cycle arrest, suggesting the possibility of CPT being developed as an agent for pancreatic cancer therapy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results from a study by Chen et al suggested that CPT is a potential drug for the treatment and prevention of human lung cancer (25). The results of our previous study indicated that CPT remained potent in tumor cells with an MDR phenotype, suggesting its potential application in cancer exhibiting a high level of chemotherapeutic resistance (12). In the present study, CPT significantly decreased the viability of the BxPC-3 pancreatic cancer cells via the induction of apoptosis and cell cycle arrest, suggesting the possibility of CPT being developed as an agent for pancreatic cancer therapy.…”
Section: Discussionmentioning
confidence: 71%
“…Extensive investigations have indicated that CPT may inhibit the proliferation of cancer cells in vitro and reduce the growth and metastases of tumors in vivo (11)(12)(13). CPT inhibits the function of STAT3 though inhibiting dimerization in DU145 prostate cancer cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-proliferation and pro-apoptosis activities of CT have been reported in multiple cancer cells including cervical cancer, cholangiocarcinoma, melanoma, rhabdomyosarcoma and leukemia [178–182]. CT-induced cell cycle arrest and apoptosis were in association with up-regulation of P53 and P21, and decreases of cyclin A 1 , cyclin B 1 , cdc2 and survivin [178–180].…”
Section: Anti-cancer Activities Of Tanshinonesmentioning
confidence: 99%
“…In prostate cancer cells, CPT induced cell apoptosis by suppressing mammalian target of rapamycin (mTOR)-mediated cyclin D1 expression [12] and inhibiting Stat3 activity [13]. In myeloid leukemia cells, CPT induced apoptosis by inhibiting the eukaryotic initiation factor 4E (eIF4E) regulatory system [14] and through ROS-dependent activation of caspase-8 and p38 MAPK [15]. While the anticancer activities of CPT against diverse types of cancer cells have been reported, the efficacy and molecular mechanisms of CPT remain unclear in colorectal cancer cells.…”
Section: Introductionmentioning
confidence: 99%